Hardness and Microstructure Characteristics in Iron Sand Casting from Ampenan Beach with Used Canned Aluminum Alloy - Angga Wildan Habibi; Sinarep Sinarep; Anak Agung Alit Triadi (Journal of Business, Social and Technology, 2025)
Background: Iron sand from Ampenan Beach, Lombok, containing approximately 74.5% Fe₃O₄, has significant potential as a locally sourced raw material for metal casting. However, its mechanical properties, particularly hardness and microstructural uniformity, often require improvement to meet industrial application standards. One promising approach to enhance these properties is alloying with recycled aluminum materials. Objective: This study aims to investigate the effect of adding recycled aluminum on the hardness and microstructural characteristics of iron sand castings. Methods: The experiment was conducted using a Completely Randomized Design (CRD) with aluminum content variations of 0%, 2%, 4%, 6%, and 8%, each repeated three times. The aluminum used was sourced from recycled beverage cans with a purity of 98.7%. Hardness testing was performed using Brinell, Rockwell, and Vickers methods, while microstructural analysis was carried out using optical microscopy. Results: The results indicate that aluminum addition significantly enhances material hardness. The optimum result was achieved at 6% aluminum content, resulting in a 28.8% increase in Brinell hardness compared to the control sample. Microstructural refinement was also observed, characterized by a reduction in grain size from 50.0 µm at 0% Al to 25.0 µm at 6% Al, the formation of a ferritic matrix with evenly distributed Al₄C₃ and Fe₃Al phases, and a transformation in graphite morphology from lamellar to nodular. However, excessive aluminum addition (8%) led to a reduction in hardness due to over-alloying and phase clustering. Conclusion: Optimizing the addition of recycled aluminum, particularly at a 6% composition, effectively improves the mechanical performance and microstructural quality of iron sand castings. These findings highlight the potential of recycled aluminum alloys to enhance the performance of locally sourced cast materials while supporting sustainable practices in metallurgy.